7. Cathodal transcranial direct current stimulation reduces seizure frequency and modulates brain functional connectivity with drug-resistant temporal lobe epilepsy: A sham controlled study. Issue 12 (December 2017) - Assenza, G.; Cottone, C.; Tecchio, F.; Pellegrino, G.; Campana, C.; Porcaro, C.; Cancelli, A.; Assenza, F.; Di Pino, G.; Tombini, M.; Di Lazzaro, V.
Abstract : Cathodal transcranial direct current stimulation (ctDCS) is a technique able to non-invasively inhibit cortical excitability, which is abnormally increased in epilepsy, but its efficacy in reducing seizures and in modulating epileptic network is still under debate. We evaluated the efficacy of 20-min 1 mA ctDCS vs sham-tDCS in reducing seizure frequency and in modulating the functional connectivity (FC) between epileptic focus (EF) and the other cortical areas, in 10 temporal drug-resistant epilepsy (DRE) patients. After 7 days of seizure diary, patients were randomized to either first-ctDCS or first-sham-ctDCS treatment. On day 8, patients underwent the assigned stimulation. On day 38, patients underwent the opposite stimulation. ctDCS cathode was placed over the EF with a symmetric montage. Immediately before and after stimulations, one-hour video-EEG recording was acquired. ctDCS reduced the percent weekly SF more than sham stimulation. EA changes did not differ between ctDCS respect to sham-ctDCS. FC changed after real stimulation in all patients and involved the focus in 71% of the new connections. No FC change was found after sham. Individualized ctDCS reduced seizure frequency in temporal DRE without any safety concern. FC changes may help to explain ctDCS effects on DRE patients.